THE ORIGIN OF KOREAN PROVERBS AND THEIR SPIRITUAL ANALYSIS (World Bulletin of Social Sciences, 2022)
The article discusses the role and importance of proverbs and sayings in the linguistic work of the Korean people, as well as the social and economic life of the Korean people, their way of life, as well as all important aspects of life. the connection with other examples of folklore and their analysis in terms of meaning and content